TINJAUAN YURIDIS UNDANG UNDANG NOMOR 39 TAHUN 1999 TENTANG HAK ASASI MANUSIA TERHADAP LESBIAN,GAY, BISEKSUAL DAN TRANSGENDER (LGBT) DI INDONESIA - Purnami, A.A. Ayu Nanda Wira; Wiryawan, I Wayan Gde (Jurnal Hukum Mahasiswa, 2024)
The phenomenon of deviating from sexual orientation or the lifestyle of modern society which is familiar with the concepts of Lesbian, Gay, Bisexual, Transgender, hereinafter referred to as LGBT) in Indonesia itself, LGBT has become a big issue in recent years. The issue raised is how to regulate Lesbian, Gay, Bisexual and Transgender (LGBT) in Law No. 39 concerning human rights for Lesbian, Gay, Bisexual and Transgender (LGBT) and how Lesbian, Gay, Bisexual and Transgender (LGBT) exist. Viewed from a human rights perspective. The type of research used is a normative juridical research method by examining laws and regulations with the problem being studied. The results of the discussion explained that the law in Indonesia clearly does not condone LGBT, let alone deviations in behavior or ideology as legal reasons why LGBT should be rejected.